City in transition: Urban open innovation environments as a radical innovation. - Peek, Gert-Joost; Troxler, Peter (My University, 2014)
In this paper we apply the transition prespective to the field of urban development. As many sectors of our society the field of urban development is undergoing major changes. Commom ways of working and traditional business models fail under the present economic circomstances and are not able to answer to the challenges that climate change, peak oil and the shortage of rare earth minirals present. We view new approaches to the process of urban area development and the introduction of the Smart City concept as prominent examples of potential transitional change in urban development and explore their possible synergies. In order to do so, we use the key concept of radical innovation and find that Urban Open Innovation Environments, such as Fab Labs, have most transitional potential. We conclude with some examples of these environments in the city of Rotterdam and preliminary success factors.
Keywords: Stadtentwicklungsplanung; Standort; Innovation; Sozialwandel; Nachbarschaft; Werkstatt; Produktion; Forschung; Öffentlichkeit; Transition; Smart City; Kreativwirtschaft; Forschungseinrichtung